In utero tobacco smoke exposure, DNA methylation, and asthma in Latino children. Issue 3 (June 2019) - Neophytou, Andreas M.; Oh, Sam S.; Hu, Donglei; Huntsman, Scott; Eng, Celeste; Rodríguez-Santana, José R.; Kumar, Rajesh; Balmes, John R.; Eisen, Ellen A.; Burchard, Esteban G.
Abstract : Background: Maternal smoking during pregnancy is a risk factor for chronic disease later in life and has been associated with variability of DNA methylation at specific cytosine-phosphate-guanine (CpG) loci. We assessed the role of DNA methylation as a potential mediator of adverse effects of in utero tobacco smoke exposures on asthma outcomes in Latino children from the US mainland and Puerto Rico. Methods: Relationships between self-reported exposure and DNA methylation at CpG loci previously reported to be associated with maternal smoking were assessed in a subsample consisting of 572 children aged 8–21 years (310 cases with asthma, 262 healthy controls), sampled from a larger asthma case-control study. Subsequently, we assessed associations between top loci and asthma-related outcomes, followed by mediation analysis for loci for which associations with outcomes were observed. Results: Self-reported maternal smoking was associated with a −1.5% (95% confidence interval (CI) = −2.4%, −0.6%) lower methylation at CpG locus cg05575921 on the AHRR gene; a 1% increase in DNA methylation at the same locus resulted in an odds ratio (OR) of 0.90 (95% CI = 0.83, 0.96) for the odds of asthma. The OR for the indirect effect of maternal smoking on asthma mediated through methylation at the cg05575921 locus was 1.18 (95% CI = 1.07, 1.68), compared to the OR for the total effect of exposure in the parent study of 1.48 (95% CI = 1.03, 2.11). Conclusions: Our findings suggest potential mediation by DNA methylation in the association between maternal smoking during pregnancy and asthma status. Abstract : Supplemental Digital Content is available in the text.